Prediction Model of Thermal Thawing Sensibility and Thaw Depth for Permafrost Embankment along the Qinghai-Tibet Engineering Corridor Using MODIS Data - Fuqing Cui; Jianbing Chen; Zhiyun Liu; Wu Zhu; Wei Wang; Wei Zhang (Journal of Sensors, 2020)
The aim of this paper was to reveal the distribution law of permafrost thermal thawing sensibility and thaw depth caused by road construction in Qinghai-Tibet engineering corridor (QTEC). The prediction models of permafrost thermal thawing sensibility and thaw depth have been developed by incorporating the MODIS and in situ soil temperature observation data. The comprehensive earth-atmosphere-coupled numerical models of different embankment structures have been utilized to calculate the thaw depth of the underlying permafrost foundation. Finally, using the given data and above developed prediction models, the distribution maps of permafrost thermal thawing sensibility and thaw depth in QTEC are obtained by grid calculation. The results show the following: (1) Insensitive permafrost of QTEC mainly distributes in the large-scale mountain and high latitude area, and highly sensitive permafrost is located in the perennial river bed, flood plain, and terrace regions. (2) Road construction has a strong thermal disturbance to underlying permafrost, and the proportion of large thaw depth area of separate embankment is obviously smaller than that of 26 m full-width embankment. (3) Increase of subgrade interval reduces the proportion of large thaw depth areas, and the application of separate embankment structure is an effective engineering means for the Qinghai-Tibet expressway.